Tempo para acesso ao tratamento do câncer de mama no Distrito Federal, Brasil Central - Barros, Ângela Ferreira; Uemura, Gilberto [UNESP]; de Macedo, Jefferson Lessa Soares (My University, 2013)
PURPOSE: To analyze the time between the first symptom and treatment in patients treated for breast cancer in public hospitals in the Federal District. METHODS: This was a cross-sectional analysis. We interviewed 250 women diagnosed with breast cancer treated in six hospitals of the State Department of Health of the Federal District from November 2009 to January 2011. The time intervals studied were the time between the detection of the symptoms and treatment subdivided into intervals until and after the first medical appointment. The variables were: age, menopausal status, color, educational level, average monthly household income, origin, reason for the initial consultation, staging, tumor size, laterality, metastasis to axillary lymph nodes, neoadjuvant chemotherapy, and type of surgery. The Mann-Whtney test was used to assess the association of these variables with the time intervals until treatment. RESULTS: The mean age was 52 years, with a predominance of white women (57.6%), from the Federal District (62.4%), with a family income of up to 2 minimum wages (78%), and up to four years of schooling (52.4%). The staging of the disease ranged from II to IV in 78.8% of the women. The time between the first symptom and treatment was 229 days (median). After detection of the first symptom, 52.9% of the women attended a consultation within 30 days and 88.8% took more than 90 days to start treatment. Women with elementary school education had a greater delay to the start of treatment (p=0.049). CONCLUSIONS: There was a significant delay to start treatment of women with breast cancer in public hospitals of the Federal District, suggesting that efforts should be made to reduce the time needed to schedule medical appointments and to diagnose and treat these patients.
Interval for access to treatment for breast cancer in the Federal District, Brazil
Keywords: Breast neoplasms/diagnosis; Breast neoplasms/therapy; Delayed diagnosis; Health services accessibility